Smart watch - Noor, Qan’eer; Yasmeen, Omar (My University, 2017)
This project which is a smart watch aims to control our times , remind us with our activities , make our lives more accurate . The smart watch has many functionalities . first of all, it controls the working time of electrical devices , save the times for the medicine to be taken ,and when the time came, there is a robot will bring the medicine .Also there is a smart to-do list to manage user tasks that need to be done in specific time . Now days we have many clocks, alarms and other tools used for time . but the idea is to have a complete time system that take care of different sides of our daily life and make things easier for us using different technologies and designing ways .